PENGGUNAAN METODE PEMBERIAN TUGAS DALAM MENINGKATKAN MOTIVASI BELAJAR PKN SISWA KELAS VI SDN 024 TARAI BANGUN KABUPATEN KAMPAR - Yuhelmeini Yuhelmeini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the lack of motivation to learn PKN sixth grade students of SDN 024 Tarai Bangun. This study aims to determine the increase motivation to learn PKN sixth grade students of SDN 024 Tarai Build Kampar through Giving Methods Task, which is carried out for 1 month. The subjects were sixth Grade SDN 024 Tarai Bangun by the number of students as many as 24 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the analysis and discussion before it can be concluded that with the implementation of such a method the task may increase motivation to learn civics class VI students at SDN 024 Tarai Bangun. Increasing student motivation seen in the first cycle is high achieving a score of 78, with an average of motivation to learn by 54.2%. While on the second cycle reached a score of 111 with an average student motivation by 77.1% and classified as very high. Although the application of the methods of the task is still no indicators have yet mencapi criteria for success or below 75%, which is the second indicator (2) an increase in the effort to learn, but an outline and in the last indicator (6) studied seriously suffered, student motivation has managed to reach 77.1% of the benchmark used is the average over 75%